Uma fotografia, múltiplas imagens: a educação rural no norte do Brasil - ARAÚJO, Sônia Maria da Silva (2015)
The article addresses the processes by which schools have been established and institutionalized on extensive-grazing ranches in rural Soure, Marajó Island, Brazil. Emergence of these schools has been tied to large landholdings and to the political relations between ranchers, vaqueiros, and government. Theoretical reflections, social data, and events are placed side-by-side with photographs that depict the fragile state of public education available to children living in the rural areas of far northern Brazil.